Pengaruh Job Satisfaction dan Work Family Conflict terhadap Turnover Intention dan Komitmen Organisasi - Danu Digdo Wicaksono (Nomicpedia: Journal of Economics and Business Innovation, 2022)
The study used a library research method involving several previous research journals. Organizations in Indonesia face a high level of competition between business entities. To overcome this, organizations need to prepare human resources properly. Demand and intense competition in the market make it difficult for organizations to find the right type of employees. This shortage of human resources must be taken into account by the organization of employees who contribute to the company. On the other hand, organizations want their employees to be involved in the organization and work. Organizations always feel the intention to rotate because of factors that affect employees, making them feel inferior and comfortable continuing to work in the organization. Work-family conflict is one aspect that affects the willingness of employees to leave the company where they work